Dampak Terapi Terintegrasi pada Kemampuan Belajar Anak dengan Gangguan Perkembangan: Sebuah Kajian Literatur - Abdul Aziz; Yusuf, Muhammad; Nur Effendi, Muhammad (Jurnal Ilmiah Edukatif, 2025)
The purpose of this study was to evaluate the impact of integrated therapy on the learning abilities of children with developmental disorders. The research method used in this study was the literature method. The results showed that children with developmental disorders often have difficulty learning. This can affect their academic performance and overall development. To address this problem, experts have developed various types of therapy. One promising approach is integrated therapy. Integrated therapy combines several types of therapy in one programme. For example, speech therapy, occupational therapy, and behavioural therapy can be combined. The goal is to help the child holistically, not just focus on one aspect. Much research has been done to see the effectiveness of integrated therapy. The results are quite positive. Children who participate in this therapy generally show improvement in various aspects. They find it easier to concentrate, communicate better, and their motor skills improve. In fact, their social and emotional abilities also improve. Even so, there is still a lot to learn about integrated therapy. For example, how best to apply it to children with different disorders. Also, more research is needed on how this therapy works in the long term. Overall, integrated therapy seems to be a good option to help children with developmental learning disabilities. However, further research is still needed to maximise its benefits.